Principles of foundation engineering, SI - Das, Braja M. 1941- (Cengage, 2024)
"Das' best-selling PRINCIPLES OF FOUNDATION ENGINEERING, 10th Edition with WebAssign digital resources introduces civil engineering students to the core concepts and applications of foundation analysis and design with current research, state-of-the art practices from the field and more worked-out problems and examples than any other resource of its kind." --
Last three editions: 2019, 2016, 2011
Keywords: Gründung -- Bauwesen; Grundbau